An introduction to R. Schürmann’s topological analytics: perspectives on the use of the concept of "hegemonic phantasm" for critical studies of corporate culture - Remizovskyi, Artem (Ukrainian Cultural Studies, 2025)
Background. Critical studies of corporate (organizational) culture have traditionally aimed to uncover hidden dynamics of power. However, a tendency toward a vulgar analysis is often present, one that reduces the motivations of dominant agents to simplistic terms and overlooks their internal logic and meaning-making foundations. To overcome this reductiveness, the article turns to Reiner Schürmann’s topological analytics – particularly his concept of the "hegemonic phantasm" – as a potential tool for modifying critical approaches to corporate culture. The aim of the study is to explore the applicability of this concept within cultural studies research on corporate culture.Methods. The study employs the historical-philosophical method for analyzing Schürmann’s texts, as well as case studies of specific conflicts in corporate culture to extrapolate the concept of the "hegemonic phantasm" onto socio-cultural reality. In addition, elements of discourse analysis and comparative interpretation of the ideas of Schürmann and Alain Badiou are utilized.Results. The concept of the "hegemonic phantasm", as formulated by Schürmann, refers to a sovereign, self-instituting principle that defines the hierarchy of meanings within a cultural field and serves as a transregional canon structuring processes of naming and identification. The article demonstrates how this concept can be used not only to critically analyze corporate culture but also to reveal conflicts between dominant narratives and excluded singularities. Examples from Ukrainian educational discourse and the theater sphere are examined to illustrate clashes between hegemonic phantasms.Conclusions. The concept of the hegemonic phantasm has the potential to transform discourse analysis of corporate culture by introducing sensitivity to narrative plurality and conflict, while avoiding reductive explanations of power dynamics to external factors. However, it also has methodological limitations: (1) its application focuses on intra-discursive structures and does not account for the material dimensions of hegemony; (2) its political neutrality raises doubts about its effectiveness in driving applied reform. Thus, the article positions itself as an introduction to Schürmann’s topological analytics and opens a perspective for further research in this direction.
Keywords: discourse analysis, power dynamics, narrative universality, exclusion, university, higher education, agent